Employers' and graduates perception survey on employability and graduateness: products of the School of Construction Economics and Management at the University of the Witwatersrand - Mtebula, Celiwe Tati (My University, 2015)
In 2009 an article titled “Crisis hits another WITS department” appeared in the Business Day newspaper. The article was based on the results that came from an internal quality review performed by the university on the School of Construction Economics and Management. The issues pertaining to the article were that the school was experiencing a shortage in staff that led to the deterioration of standards and the quality of graduates in the year 2008 and 2009. The School of Construction Economics and Management is a major source of young professionals into the built environment, which is important for the country’s ability to deliver infrastructure projects. This research examines the graduateness and employability of graduates that were produced from the school in the period between 2008 and 2011. Questionnaires were sent out to graduates and employers in order to find out what the perceptions were of both the concept of graduateness and employability. The key findings were that whilst the graduates said that they were ready for employment after completion of their respective degrees, the employers said that graduates did not have sufficient experience to enter the working world. Thus it is clear a gap certainly exists between the perceptions of graduates and employers. It was concluded that an effort must be made between the different stakeholders to breach this gap.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of: Master of Science in Building (Project Management in Construction)
Keywords: Construction industry--Management; Skilled labour--South Africa; Skills development--South Africa